A Prelimenary Study About Happiness At Work Of Civil Servants In DKI JAKARTA - Puji Tania Ronauli; Euginia Natasha (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2021)
This study is designed to describe the meaning of happiness at work and its five factors (contributions, conviction, culture, commitment, and confidence) by Jones (2010) for civil servants in DKI Jakarta. This study uses a qualitative method with purposive sampling technic. This research examines five participants of civil servants with various background. Four participants come from Directorate General of Taxes and the other is from Ministry of Law and Human Rights. Two participants are female and three participants are male with age range 28 to 58 years. Data were collected over ten weeks period through interview, observation, triangulation and coding. Each interview is taken minimum 80 minutes. The results showed that happiness at work was defined as a positive emotion that comes from a person who felt comfortable with his work environment and organizational culture. Further, the positive emotions might cause a civil servant to undergo a job without felt depressed so s/he could actualize her/himself through her/his work. Several factors that shape happiness at work are good relationship with colleagues and superiors, motivation, challenging or varied work, and a feeling of being suitable or in accordance with the work undertaken. The discussion discussed the differences in the results of research with happiness at work theory by Jones (2010) and the linkages of factors that shape happiness at work with Indonesian culture standard.